Komparasi Kurikulum Merdeka Belajar Dan Al-Quran Surat Al Baqarah Ayat 31 - Baktiar Leu (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
This research is aimed to discuss comparison of independent learning curriculum and Al-Quran of Al-Baqarah verse 31, which discusses about the concept of independent learning curriculum, the meaning of the independent learning curriculum according to the Ministry of Education and Culture, and based on Al -Quran of Al-Baqarah verse 31. This paper is library research, with a multidisciplinary approach, (pedagogical, psychological, sociological and normative theological. The independent learning curriculum means that learning must build the will and spirit, freedom to express one's thoughts and all forms of fear. Students are expected to grow up and develop their potential and abilities. Through the independent learning curriculum, students are expected to have literacy skills (reading, and analyzing), Numeration (discussion material, application the numeration concepts to life, individual or social). And a character survey to know students as individuals, as well as the application of religious values, Pancasila and moral values. Compere with Al-Baqarah verse 31 that Allah has taught concepts and understanding and introduced to Adam the names of natural objects, expressed through language. This means that Adam was taught to capture concepts and explain them to humans. so that Adam as has mastered symbols to think and analyze, communicate and accept the knowledge, internalization of values ??and at carry out scientific studies (literacy, numeration and character surveys) through the senses (zahir, inner and heart).